Psychological States and Mental Health Stigma as Predictors of Help-Seeking Attitude among Selected Combat Military Personnel: Basis for a Mental Wellness Intervention Program - Abraham, Valerie (Journal of Interdisciplinary Perspectives, 2025)
Mental health challenges are a growing concern among military personnel worldwide, particularly those exposed to combat. In the Philippines, there is an urgent need for better psychological support systems to help them cope and prevent serious consequences. This study explored what predicted military personnel’s willingness to seek help for mental health concerns, focusing on those who have been previously or currently deployed in combat. Using a descriptive correlational research design, standardized screening tools, and stepwise multiple regression analysis, the study examined how psychological states (depression, anxiety, and stress) and mental health stigma predicted help-seeking attitudes. The findings revealed that higher depression, stress, and mental health stigma levels were linked to a greater reluctance to seek support with a p-value of <.05. Among all factors, depression, and stigma were the strongest predictors of help- seeking attitudes (F =46.249, p < .05). A one-unit increase in depression led to a 0.138 decrease in help-seeking attitude. In comparison, a one-unit increase in stigma resulted in a 0.333 decrease. The respondent’s willingness to seek help was shaped by personal, social, and emotional factors, with depression and stigma playing key roles. Thus, these findings helped develop targeted intervention and support systems to encourage military personnel to seek professional mental health care when needed.